Hanle Effect for Lifetime Determinations in the Soft X-Ray Regime - Togawa, Moto (2024)
Grant No. UID/FIS/04559/2020 (LIBPhys). Financial support was provided by the Max-Planck-Gesellschaft (MPG), Bundesministerium for Bildung und Forschung (BMBF) through project 05K13SJ2 C.S. acknowledges support from MPG and NASA-JHU Cooperative Agreement. We acknowledge Elettra Sincrotrone Trieste for providing access to its synchrotron radiation facilities (long term proposals No. 20205206). Fabio Zuccaro is acknowledged for technical support during beamtime preparation and realization. J.R. and A.S. acknowledge funding by the Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) under Germany's Excellence Strategy-EXC-2123 QuantumFrontiers-390837967. Publisher Copyright: © 2024 authors. Published by the American Physical Society. Published by the American Physical Society under the terms of the "https://creativecommons.org/licenses/by/4.0/"Creative Commons Attribution 4.0 International license. Further distribution of this work must maintain attribution to the author(s) and the published article's title, journal citation, and DOI. Open access publication funded by the Max Planck Society.